Allergic enteritis in children - Mieczysława Czerwionka-Szaflarska; Ewa Łoś-Rycharska; Julia Gawryjołek (Gastroenterology Review)
The gastrointestinal form of food allergy is very common in children. The most frequently observed types are allergic proctitis and proctocolitis. In most cases the symptoms subside within the first 2 months of life. The babies seem healthy, and the only abnormality is a small amount of blood in stool. Symptoms can also include small intestine inflammation and colitis. Patients may present with irritability, abdominal pain, flatulence, colic, postprandial vomiting, chronic diarrhoea, and hindered physical development. The diagnosis of allergic enteritis is based on the clinical examination and the results of additional tests including an endoscopy of the lower digestive tract with histopathological assessment. Cow’s milk proteins are the most common nutrition proteins responsible for the development of the symptoms of allergic enteritis. The most essential method of treating allergic enteritis is the elimination diet. The symptoms should subside within 1–2 weeks from the beginning of the diet.